2018
DOI: 10.3390/v10100548
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant GII.P16/GII.4 Sydney 2012 Was the Dominant Norovirus Identified in Australia and New Zealand in 2017

Abstract: For the past two decades, norovirus pandemic variants have emerged every 3–5 years, and dominate until they are replaced by alternate strains. However, this scenario changed in 2016 with the co-circulation of six prevalent viruses, three of which possessed the pandemic GII.4 Sydney 2012 capsid. An increased number of institutional gastroenteritis outbreaks were reported within the Oceania region in mid-2017. This study identified emerging noroviruses circulating in Australia and New Zealand in 2017 to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Although, its presence does not mean that the virus is active or infectious, we cannot exclude the hypothesis that this virus can also be present in the fish flesh that can be consumed raw or undercooked in several meals, possessing a potential risk to human health. Noroviruses are the leading cause of viral gastroenteritis worldwide, and are estimated to cause 677 million cases and ≈ 210,000 human deaths every year [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, its presence does not mean that the virus is active or infectious, we cannot exclude the hypothesis that this virus can also be present in the fish flesh that can be consumed raw or undercooked in several meals, possessing a potential risk to human health. Noroviruses are the leading cause of viral gastroenteritis worldwide, and are estimated to cause 677 million cases and ≈ 210,000 human deaths every year [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the last decades, the GII.4 variant dominated NoV infections, being responsible for 60-80% of all NoV outbreaks. Therefore, in the last years, we observed the emergence of a novel GII.4 recombinant virus responsible for several outbreaks worldwide [45,46] that retained the Sydney 2012 capsid-coding sequence but acquired a new structural region (GII.P16/GII.4 Sydney 2012) [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The GII.P16 genotype has already been associated with several different capsid genotypes (GII.P16-GII.2, GII.P16-GII.3, GII.P16-GII.4, GII.P16-GII.1, GII.P16-GII.12, GII.P16-GII.10) (Ruis et al, 2017;Nagasawa et al, 2018;Barclay et al, 2019). Previous studies suggested that the GII.4_Sydney strain acquired GII.P16 from the GII.P16-GII.2 strains (Tohma et al, 2017;Lun et al, 2018). This hypothesis was supported in this study, since strains clustered closer in the temporal reconstruction tree, and the TMRCA of both strains emerged in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating GII.4 strains shared homology with emergent recombinant strain GII.P16-GII.4/RUS/ 2017 (MG892929), GII.P16-GII.4 Sydney/2012 (KY887601) and GII.P4 New Orleans/2009/GII.4/Sydney 2012 (MG585810.1) (52). The Novosibirsk-2017 strain harbors several AA changes within the main epitope of the P2 capsid domain and shares a common ancestor with the NoV GII.4 variants Apeldoorn 2008 and New Orleans 2009 [51]. On the other hand, the Sydney-2012 strain was also isolated in the United States, Denmark, Japan, and Scotland [52,53,54,55].…”
Section: Discussionmentioning
confidence: 99%